Comparison of the Implementation of Infection Prevention Before and During the Covid-19 Pandemic in Patients in the Emergency Unit of RSUD DR. M.M. Dunda Limboto - Lutvi Hairun Nissa Hasan; Andy Kurniawaty Naue; Adnan Malaha (Journal of Health, Technology and Science (JHTS), 2021)
This study aims to determine the comparison of the implementation of infection prevention before and during the COVID-19 pandemic in Patients in the Emergency Unit of RSUD DR. M.M. DundaLimboto. The research method used is the descriptive method with a qualitative approach by describing, analyzing, and discussing data directly sourced from informants. The informants in this study were 2 (two) IPCN people, the ER implementers consisted of the head of the ER, 1 doctor, 1 nurse, and the management, namely the head of the field of medical services. The results of the study that have been carried out regarding the comparison of the implementation of infection prevention before and during the covid-19 pandemic in Patients in the Emergency Unit of RSUD DR. M.M. Dunda Limboto, it can be seen that there is a gap in the achievement of the PPI implementation target in the ER before and during the covid-19 pandemic, where this gap is more likely to be influenced by individual factors related to officer compliance which will affect the implementation of the PPI program, training that has not been carried out routinely both before and during the covid-19 pandemic, for management support in terms of providing PPE and handwashing facilities is still minimal, This led to an increase in the budget during the COVID-19 pandemic.